2011
DOI: 10.5194/acp-11-13325-2011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical characteristics of 495 biomass burning plumes intercepted by the NASA DC-8 aircraft during the ARCTAS/CARB-2008 field campaign

Abstract: Abstract. This paper compares measurements of gaseous and particulate emissions from a wide range of biomassburning plumes intercepted by the NASA DC-8 research aircraft during the three phases of the ARCTAS-2008 experiment: ARCTAS-A, based out of Fairbanks, Alaska, USA (3 April to 19 April 2008); ARCTAS-B based out of Cold Lake, Alberta, Canada (29 June to 13 July 2008); and ARCTAS-CARB, based out of Palmdale, California, USA (18 June to 24 June 2008). Approximately 500 smoke plumes from biomass burning emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 73 publications
9
91
0
Order By: Relevance
“…Mean f 44 for B626, which comprised the only measurements of fresh OA during BOR-TAS, was lower than all other flights at 0.086 ± 0.014, with mean values for B621-B624 ranging from 0.104 to 0.139. This trend between the near and far-field is consistent with observations of boreal forest fire plumes during ARCTAS, where f 44 was shown to increase as a function of plume transport time (Cubision et al, 2011;Hecobian et al, 2011). f 60 was also shown to decrease concurrently with increasing f 44 during ARCTAS, as a result of the oxidation of primary levoglucosan-type species with aging.…”
Section: Tracers For Combustion Conditionssupporting
confidence: 76%
“…Mean f 44 for B626, which comprised the only measurements of fresh OA during BOR-TAS, was lower than all other flights at 0.086 ± 0.014, with mean values for B621-B624 ranging from 0.104 to 0.139. This trend between the near and far-field is consistent with observations of boreal forest fire plumes during ARCTAS, where f 44 was shown to increase as a function of plume transport time (Cubision et al, 2011;Hecobian et al, 2011). f 60 was also shown to decrease concurrently with increasing f 44 during ARCTAS, as a result of the oxidation of primary levoglucosan-type species with aging.…”
Section: Tracers For Combustion Conditionssupporting
confidence: 76%
“…A higher O/C ratio together with a higher OS C determined for the 17 April plume, suggest the 17 April OA is more oxidized than the 29 June OA. During ARCTAS, Hecobian et al (2011) and Cubison et al (2011) found little evidence for net SOA formation in the Canadian biomass burning plumes encountered by the DC-8, although some SOA formation may have been compensated by POA evaporation. The effect of SOA formation during transport of the Siberian plume is unconstrained by the ARCTAS data, but by analogy with the Canadian plumes it is likely to have been minor.…”
Section: Aerosol Oxidation and Spectral Absorptionmentioning
confidence: 99%
“…For this reason, the ER for short-lived species should only be calculated using measurements in the freshest possible fire plumes. In aged plumes the regression slope is usually known as a normalised excess mixing ratio (NEMR) or enhancement ratio instead Hecobian et al, 2011;Akagi et al, 2011Akagi et al, , 2012Le Breton et al, 2013;Yokelson et al, 2013).…”
Section: Enhancement Ratios and Emission Factorsmentioning
confidence: 99%